The Role Of Educators In Instilling Environmental Awareness In Students At The Ihya Ulumuddin Nur Sufiiyah Islamic Boarding School (IUNS) In Amuntai - Mulia; Muhammad Ikhsan; Maulana Sasty (Journal Innovative Practices in Education (JIPE), 2025)
Environmental awareness is part of Islamic values ​​that teach balance and human responsibility as khalifatullah. This study aims to explain how teaching, guidance, and habituation are given by educators in an effort to foster environmental awareness based on Islam in the Ihya Ulumuddin Nur Sufiiyah (IUNS) Amuntai Islamic Boarding School environment. This study uses a qualitative method. The subjects of the study were caregivers, ustadz/ ustadzah, dormitory supervisors, senior students and cleaning staff. Data were collected through observation, interviews, and documentation. The research data analysis technique used the Miles and Huberman interactive model. Data validity was checked through triangulation. The results of the study showed that the role of educators in instilling environmental awareness. First, through the integration of learning moral values ​​towards the environment in the classroom. Second, teacher role models are the main factor in the success of teaching environmental awareness. Third, the existence of environmentally friendly behavior habits. This study found that the combination of school curriculum, Islamic boarding school curriculum, and daily activities in Islamic boarding schools can be a holistic method in educating students to care about the environment. This study recommends this holistic method as a strategy to create a generation with broad insight based on Islamic values.